2016
DOI: 10.13069/jacodesmath.01767
|View full text |Cite
|
Sign up to set email alerts
|

On the spectral characterization of kite graphs

Abstract: The Kite graph, denoted by Kite p,q is obtained by appending a complete graph K p to a pendant vertex of a path P q . In this paper, firstly we show that no two non-isomorphic kite graphs are cospectral w.r.t adjacency matrix. Let G be a graph which is cospectral with Kite p,q and the clique number of G is denoted by w(G). Then, it is shown that w(G) ≥ p − 2q + 1. Also, we prove that Kite p,2 graphs are determined by their adjacency spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
0
4
0
4
Order By: Relevance
“…Eğer > + 1 ise , − grafına uzun uçurtma graf denir [1,3]. Lolipop graf ise p noktalı bir döngü grafın, n-p noktalı bir yol grafın bir dereceli noktasına yeni bir kenar yardımıyla bağlanması ile elde edilir [9].…”
Section: Introductionunclassified
See 3 more Smart Citations
“…Eğer > + 1 ise , − grafına uzun uçurtma graf denir [1,3]. Lolipop graf ise p noktalı bir döngü grafın, n-p noktalı bir yol grafın bir dereceli noktasına yeni bir kenar yardımıyla bağlanması ile elde edilir [9].…”
Section: Introductionunclassified
“…Dolayısıyla bu durum uçurtma grafında aynı özelliklere sahip olup olmadığının araştırılması konusunda motivasyon kaynağı teşkil etmektedir. Kısa uçurtma grafın DAS ve DLS olduğu gösterilmiştir [1,2]. Ayrıca ≥ 4 ve ≠ 5 iken ,1 grafın işaretsiz Laplasyan matrisinin spektrumuna göre belirlenebilir olduğu da gösterilmiştir [3].…”
Section: Introductionunclassified
See 2 more Smart Citations
“…Similarly, by appending a complete graph to a pendant vertex of a path, we obtain the Kite graph. In [20], the adjacency characteristic polynomial of the Kite graph is calculated and it is shown that the Kite 2 p graph is determined by its adjacency spectrum. Also it is conjectured that the Kite q p graph is determined by its adjacency spectrum for all p and q.…”
Section: Introductionmentioning
confidence: 99%